Postgraduate theses in forensic dentistry in Türkiye: a methodological evaluation - Duman, Burcu (The Bulletin of Legal Medicine, 2025)
Objective: This study aims to examine the methodological status of postgraduate theses in forensic dentistry in Türkiye. Since there is no comprehensive evaluation of this field in the literature, the research fills an important gap.Methods: Theses completed between 1999 and 2025 were retrieved from the Turkish National Thesis Center (www.tez.yok.gov.tr) using the keywords “Forensic Dentistry,” “Forensic Odontology,” “Forensic Sciences and Dentistry,” and “Forensic Medicine and Dentistry.” Data were analyzed through frequency distributions and Chi-square tests.Results: A total of 41 theses were evaluated: 7 master’s, 16 doctoral, 16 dentistry specialization, and 2 medical specialization. The highest output was in 2022 (19.5%). Most studies were conducted in state universities (92.7%), with a smaller proportion in private institutions (7.3%). Female researchers (58.5%) contributed more than males. Professors dominated supervisory roles (61%). Radiographic identification methods were the most common topic (46.3%), while AI-based and legal studies remained limited (9.8%). Laboratory-based research (31.7%) was the most frequent design.Conclusion: Postgraduate studies in forensic dentistry in Türkiye lack methodological diversity, show limited adoption of innovative techniques (9.8%), and are regionally concentrated (46.3% in Central Anatolia). Interdisciplinary collaborations and methodological training are recommended to overcome these limitations.
Keywords: Postgraduate Education; Thesis; Forensic Sciences; Dentistry; Forensic Odontology